Continuous radiofrequency in post-traumatic trochanteric syndrome - Dario Giaime (Pathos)
Trochanteritis is a disorder that primarily affects individuals over the age of 50, with a higher prevalence among women. However, it can also occur in other age groups, particularly among athletes engaged in activities such as running, cycling, and brisk walking. The pain associated with trochanteritis is localised to the hip and upper thigh. If left untreated, it can become a significant source of disability. The following case study presents the clinical course of a patient with trochanteritis who exhibited resistance to drug therapies. TThe patient underwent continuous radiofrequency treatment at our centre, which resulted in positive outcomes in terms of pain and walking.